EXPLORING THE EFFECT OF USING ARABIC LANGUAGE IN TEACHING ENGLISH AS A FOREIGN LANGUAGE TO LIBYAN MIDDLE STAGE STUDENTS AT SEBHA CITY (Journal of Human Sciences, 2025)
This paper aims at exploring the effect of using Arabic language for teaching English as a Foreign Language in a Libyan context at middle school stage in Sebha city. English language teachers in Sebha middle schools usually rely on using Arabic language more than English language in their classes, but they come across a problem which is the lack of communication between the teachers and their students in the target language due to students’ difficulties in communicating in English. The current study sample consists of 10 participants. The researchers used random sampling to select the participants of the study form three middle schools in the city of Sebha. The researchers used an interview technique to elicit data from the participants. The findings of the research indicated that using (L1) Arabic language in English classes affects Libyan middle school students’ effective mastery of L2 in a negative way when learning English as a foreign language within a classroom setting in a Libyan context. This paper recommends further research to be conducted to explore relevant types of problems related to this study with different areas.